Case Report: First case of a pediatric laryngeal inflammatory rhabdomyoblastic tumor—diagnostic dilemma and insights into the conservative management of a residual lesion - M. S. Nadhirah; M. S. Nadhirah; A. Hamidah; A. Hamidah; A. A. Aishah Harizah; A. A. Aishah Harizah; R. M. Z. Reena; R. M. Z. Reena; T. Y. Kew; T. Y. Kew; M. B. Marina; M. B. Marina (Frontiers in Pediatrics)
An inflammatory rhabdomyoblastic tumor (IRMT), formerly known as a histiocyte-rich rhabdomyoblastic tumor (HR-RMT), has been identified as a skeletal muscle neoplasm exhibiting a mild clinical course. However, recent studies suggested that an HR-RMT has significant pathological and genetic overlap with inflammatory leiomyosarcoma, leading to the proposal of the newly defined entity, IRMT. We report the first case of an IRMT affecting the larynx in an adolescent girl who presented with a 3-month history of hoarseness. Endoscopic examination revealed a left paraglottic mass, which was surgically removed. No disease progression was observed over a 4-year follow-up. We discuss the diagnostic and management challenges, especially the role of adjuvant therapies in pediatric patients. This case highlights the importance of a precise diagnosis and careful management and emphasizes the need to increase awareness of IRMT.